2017
DOI: 10.5114/biolsport.2017.67122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different jumping tests in defining position-specific and performance-level differences in high level basketball players

Abstract: The importance of jumping ability in basketball is well known, but there is an evident lack of studies that have examined different jumping testing protocols in basketball players at advanced levels. The aim of this study was to assess the applicability of different tests of jumping capacity in identifying differences between (i) playing position and (ii) competitive levels of professional players. Participants were 110 male professional basketball players (height: 194.92±8.09 cm; body mass: 89.33±10.91 kg; 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 24 publications
6
75
0
4
Order By: Relevance
“…Somatotypology aims at classifying athletes into several somatotypes (endomorph, ectomorph and mesomorph) for the purpose of selecting athletes for certain sports. Some studies indicate that the endomorph somatotype is not suitable for basketball (22), whereas other studies confirm that the ectomorph type has predispositions for those sports. Ectomorphs are tallish and characterized by relatively longer bones, which makes them suitable for sports which require tall players (high jump, basketball, volleyball, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Somatotypology aims at classifying athletes into several somatotypes (endomorph, ectomorph and mesomorph) for the purpose of selecting athletes for certain sports. Some studies indicate that the endomorph somatotype is not suitable for basketball (22), whereas other studies confirm that the ectomorph type has predispositions for those sports. Ectomorphs are tallish and characterized by relatively longer bones, which makes them suitable for sports which require tall players (high jump, basketball, volleyball, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Jumping ability of male youth basketball players tested in this study demonstrated lower mean values of the SJ 28.9 ±5.4 (cm) and CMJ 34.4 ±6.2 (cm) than reported by Köklü et al (2011) among Turkish first (SJ (cm) 37.8 ±5.7; CMJ (cm) 40.6 ±4.7) and second (SJ (cm) 34.7 ±5.7; CMJ (cm) 36.0 ±5) division professional basketball players. Even higher performance of CMJ (cm) 45.5 ±5.6 has been shown among professionallevel male basketball players from Bosnia and Herzegovina (Pehar et al, 2017). A study presented by Schiltz et al (2009) concerning the height of the CMJ did not reveal significant differences between groups of professional basketball players 40.5 ±5.7 (cm) and juniors 41.8 ±5.8 (cm).…”
Section: Discussionmentioning
confidence: 88%
“…Köklü, et al (2011) observed selection of physical fitness characteristics of Turkish professional basketball players and found, among others, that the height of the Squat jump (SJ) was 36.2 ± 5.5 cm and CMJ 38.3 ± 5.3 cm. Along with other indicators Pehar et al (2017) has examined jumping performance of professional-level male basketball players from Bosnia and Herzegovina and found that the height of the CMJ was 45.5 ±5.6 cm on average. In both studies jump tests were performed keeping their hands on their hips.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant characteristic for success in basketball is the longitudinal dimension of the skeleton, followed by the transversal dimension of the skeleton and body mass. In view of the specific structure of basketball, subcutaneous fat tissue appears strongly as a negative feature, that is, a factor that distorts the competitive activity of female and male basketball players (Ziv & Lidor;Pehar et al, 2017;Garcia-Gil et al;Ramos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%